4346 Potential Sudden Unexpected Death in Epilepsy (SUDEP) Biomarkers in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes with DEPDC5 Loss-of-Function. Issue Volume 4:Issue(2020)Supplement 1 (June 2020) - Zhao, Yanting; Zhang, Helen; Parent, Jack M.; Isom, Lori L.
Abstract : OBJECTIVES/GOALS: Sudden Unexpected Death in Epilepsy (SUDEP) is a leading cause of death in epilepsy patients. This study aims to determine whether cardiac mechanisms contribute to SUDEP in epilepsy patients with variants in DEPDC5, a gene encoding a member of the mTOR GATOR complex, to identify SUDEP biomarkers. METHODS/STUDY POPULATION: SUDEP has been reported in 10% of epilepsy patients with DEPDC5 loss-of-function variants. We used human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) to measure changes in cellular excitability that are known to be substrates for cardiac arrhythmias. CRISPR-derived isogenic DEPDC5 iPSC-CMs and DEPDC5 patient-derived iPSC-CMs were used in this study. Whole-cell patch-clamp was used to measure voltage-gated sodium current ( I Na ) and calcium current ( I >Ca ) in single iPSC-CMs in voltage-clamp mode; and to measure action potentials (APs) in 3-dimentional iPSC-CM-derived micro-tissues in current-clamp mode. RESULTS/ANTICIPATED RESULTS: CRISPR generated heterozygous deletion of 1 base-pair in the first coding exon of DEPDC5 gene, resulting in a premature stop codon, simulated the variants identified in DEPDC5 epilepsy patients. In CRISPR generated heterozygous DEPDC5 iPSC-CMs, whole-cell voltage-clamp recordings revealed that I Na was increased and I Ca was reduced compared with isogenic control iPSC-CMs. Whole-cell current-clamp recordings revealed that AP duration at 80% and 90% of repolarization, APD80 and APD90, respectively, were prolonged compared to isogenic control iPSC-CMs. Similar measurements will be performed for iPSC-CMs derived from DEPDC5 patients. DISCUSSION/SIGNIFICANCE OF IMPACT: This study shows that epilepsy patients with non-ion channel gene variants in DEPDC5 have altered CM excitability, which may serve as a substrate for cardiac arrhythmias in DEPDC5 patients. Importantly, this work may allow us to identify biomarkers for SUDEP risk in these patients in the future. CONFLICT OF INTEREST DESCRIPTION: L.L.I. is the recipient of a collaborative research grant from Stoke Therapeutics.